CYTOKINE PROFILE AND ADHESION MOLECULES IN THE PATIENTS WITH CHRONIC OBSTRUCTIVE LUNG DISEASE COMBINED WITH BRONCHIAL ASTHMA - T. G. Shapovalova; M. V. Volkova; N. V. Shelobanova (Медицинская иммунология)
The study involved 56 patients with chronic obstructive pulmonary disease (COPD), stage III-IV, 38 patients with severe bronchial asthma (BA), and 45 patients with a combination of COPD stage III-IV and bronchial asthma at exacerbation period. In all the patients, we have measured blood levels of pro-inflammatory (IL-6, IL -8, TNFα) and anti-inflammatory (IL-4) cytokines, amounts of cell adhesion molecules (ICAM- 1, VCAM-1), along with assessment of contractile myocardial functional disorders by means of Doppler echocardiography. Highest rates of pro-inflammatory cytokines and adhesion molecules were found in the group of patients with combined pathology, along with most significant signs of myocardial hypertrophy, both in right and left heart compartments, accompanied by a decrease in contractile myocardial function.